Small bowel Crohn’s disease: MR enteroclysis and capsule endoscopy compared to balloon-assisted enteroscopy - Wiarda, Bart M. (Springer-Verlag, 2011)
New modalities are available to visualize the small bowel in patients with Crohn’s disease (CD). The aim of this study was to compare the diagnostic yield of magnetic resonance enteroclysis (MRE) and capsule endoscopy (CE) to balloon-assisted enteroscopy (BAE) in patients with suspected or established CD of the small bowel. Consecutive, consenting patients first underwent MRE followed by CE and BAE. Patients with high-grade stenosis at MRE did not undergo CE. Reference standard for small bowel CD activity was a combination of BAE and an expert panel consensus diagnosis. Analysis included 38 patients, 27 (71%) females, mean age 36 (20–74) years, with suspected (n = 20) or established (n = 18) small bowel CD: 16 (42%) were diagnosed with active CD, and 13 (34%) by MRE with suspected high-grade stenosis, who consequently did not undergo CE. The reference standard defined high-grade stenosis in 10 (26%) patients. Sensitivity, specificity, positive predictive value (PPV) and negative predictive value of MRE and CE for small bowel CD activity were 73 and 57%, 90 and 89%, 88 and 67%, and 78 and 84%, respectively. CE was complicated by capsule retention in one patient. MRE has a higher sensitivity and PPV than CE in small bowel CD. The use of CE is considerably limited by the high prevalence of stenotic lesions in these patients.